Penyelesaian Persamaan Panas Dimensi Satu dengan Metode Beda Hingga Skema Eksplisit - Sanusi, Wahidah; Pratama, Muhammad Isbar; Side, Syafruddin; Fitriyani (Jurusan Matematika FMIPA UNM, 2022)
This research is a pure research in the form of a theoretical study that aims to determine the solution of the one-dimensional heat equation using the finite difference method explicit scheme and to know the simulation of the one-dimensional heat equation. The explicit schema finite difference method is an alternative method used to solve partial differential equations. The first step in this research is to build and analyze the one-dimensional heat equation. Next, discretize the one-dimensional heat equation by usingnumerical derivatives. Then solve the one-dimensional heat equation using an explicit schema. Finally, using the Matlab program to simulate the solution of the one-dimensional heat equation. The simulation results show that there is a change in temperature from a high temperature to a lower temperature which is influenced by time due to the heat transfer process.